Outdoor Recreation Environmental Impacts and Management - Huddart, David; Stott, Tim (Palgrave Macmillan, 2019)
This textbook presents a comprehensive overview of the environmental impacts of various types of outdoor recreation, and how these can be best managed. As a field of study, recreational ecology is both multidisciplinary and interdisciplinary, and the authors seek to develop a deeper understanding of both the role and function of the factors that influence visitor numbers and their impact. An accessible and comprehensive textbook, it features numerous types of outdoor recreational activities including hill walking, rock climbing, mountain marathons, skiing, scuba diving and more. Drawn from several global case studies, the authors estimate the current and future numbers involved in outdoor recreation, and how best these numbers can be managed. Effective visitor impact management actions arise from collaboration between recreation ecologists, social scientists, experienced recreation managers, recreation stakeholders and the recreationalists themselves: as such, this book will be multi-disciplinary in scope. This practical and engaging textbook will be invaluable to students and scholars of outdoor recreation and adventure tourism as well as practitioners and managers working in the field.